2014
DOI: 10.1186/1749-8090-9-48
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with ovation endograft system in abdominal aortic disease

Abstract: ObjectiveWe describe our initial experience with the use of the TriVascular Ovation endograft system for the treatment of abdominal aortic aneurysms (AAA).MethodsWe retrospectively reviewed data from patients treated for AAA using the Ovation endograft at two institutions from January 2011 to September 2012. Main outcomes included primary success, survival, complications, and device-related events. The mean follow-up period was 10 months (range 1–22 months).ResultsThirty-seven patients (male: 95%, mean age: 76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 4 publications
3
15
0
Order By: Relevance
“…No Type I, III or IV endoleak, AAA enlargement, AAA rupture, stent fracture, migration, or endovascular or surgical reintervention were reported during the follow-up period. 31 These results are comparable to ours (all-cause and AAA-related mortality 0%, technical success rate 95%, midterm clinical success rate 94%, no Type I, III, IV endoleak, no migration, open conversion required in 3% of patients), indicating overall promising results, with excellent demonstrated safety and effectiveness in patients with AAA. The two cases that needed conversion to open surgery were performed with the firstgeneration Ovation device and looking retrospectively back it is our belief that in at least one of these patients cannulation would have been feasible with the second-generation Ovation Prime™, in which the limbs are attached at the distal end to facilitate easier catheterization of the contralateral limb.…”
Section: Discussionsupporting
confidence: 73%
“…No Type I, III or IV endoleak, AAA enlargement, AAA rupture, stent fracture, migration, or endovascular or surgical reintervention were reported during the follow-up period. 31 These results are comparable to ours (all-cause and AAA-related mortality 0%, technical success rate 95%, midterm clinical success rate 94%, no Type I, III, IV endoleak, no migration, open conversion required in 3% of patients), indicating overall promising results, with excellent demonstrated safety and effectiveness in patients with AAA. The two cases that needed conversion to open surgery were performed with the firstgeneration Ovation device and looking retrospectively back it is our belief that in at least one of these patients cannulation would have been feasible with the second-generation Ovation Prime™, in which the limbs are attached at the distal end to facilitate easier catheterization of the contralateral limb.…”
Section: Discussionsupporting
confidence: 73%
“…Noteworthy, the management of the aforementioned problems associated with difficult cannulation has been markedly facilitated by the introduction of the Ovation PRIME, the newest version of the endoprosthesis, where the contralateral leg is connected to the delivery system via a trigger wire, which is designed to prevent the twisting associated with the cannulation problems. 6 As anticipated, the significance of the results in our study is limited by the small number of patients, the absence of long-term follow-up, and the simple AAA neck geometries (long necks of minor angulation). However, the technical success of the Ovation device in treatment of AAA with challenging iliac anatomies is sufficiently depicted and described in our series, and the deliberately chosen friendly neck anatomies help focusing on the comparison of outcomes with respect to the iliac diameter and angulation.…”
Section: Discussionmentioning
confidence: 85%
“…The lack of nitinol support from the main body and iliac limb gates may render the contralateral iliac limb of the endograft prone to compromisation or collapse against the AAA sac wall in cases of a tight endoluminal space due to narrow aortoiliac bifurcation and eccentric intraluminal thrombus, complicating its catheterization and increasing the intraprocedural difficulties. 6,24 In the series by Nano et al, 6 inability to catheterize the contralateral limb led to a femefem bypass surgery in 1 case. Furthermore, because the ipsilateral limb is neither fixed nor contained within the delivery catheter when the main body deploys, this can lead sometimes to twisting of the limbs with consequent difficulty in cannulation or accommodation of the crossing-limbs configuration.…”
Section: Discussionmentioning
confidence: 97%
“…This is supported by previous studies of the Ovation stentgraft that reported excellent perioperative outcomes with predominant or exclusive use of percutaneous access, with or without local anesthesia. [30][31][32][33] As fast-track EVAR evolves, development of evidence-based surgical decisionmaking algorithms would allow flexibility in patient management decisions.…”
Section: Discussionmentioning
confidence: 99%